2020
DOI: 10.1111/jcmm.15685
|View full text |Cite
|
Sign up to set email alerts
|

CircC3P1 attenuated pro‐inflammatory cytokine production and cell apoptosis in acute lung injury induced by sepsis through modulating miR‐21

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Moreover, AAV-MEF2C treatment markedly suppressed sepsis-induced ALI by modulating miR-21. 22 During sepsis, increased numbers of TUNEL-positive cells in the lung sections were observed. 23 Currently, we demonstrated that CLP challenge elevated the number of TUNEL-positive cells in the lung section, which was further reduced by the overexpression of MEF2C, suggesting the anti-apoptosis effect of MEF2C in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AAV-MEF2C treatment markedly suppressed sepsis-induced ALI by modulating miR-21. 22 During sepsis, increased numbers of TUNEL-positive cells in the lung sections were observed. 23 Currently, we demonstrated that CLP challenge elevated the number of TUNEL-positive cells in the lung section, which was further reduced by the overexpression of MEF2C, suggesting the anti-apoptosis effect of MEF2C in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings propose that circRNAs may play a role in regulating the patients' immune system, and misregulation of circRNAs might be an early event in sepsis [19][20][21]. It is well known that ARDS is one of the major consequences of septic shock [3].…”
Section: Discussionmentioning
confidence: 99%
“…Recent ndings propose that circRNAs may play a role in regulating the patients' immune system and misregulation of circRNAs might be an early event in sepsis [21,22,23] . It is well known that ARDS is one of the major consequences of septic shock [3] .…”
Section: Discussionmentioning
confidence: 99%